O racismo na trajetória escolar e profissional de professoras universitárias - CHAVES, Evenice Santos (Universidade Federal do Pará, 2011)
This research utilized an interdisciplinary theoretical and methodological apparatus and focused on social and racial disparities along the academic and professional way of female professors. Brazilian literature examined in Psychology field does not offer examples of qualitative researches about social and racial disparities with an emphasis on black and white individuals. This way, and in this context, this study was included and intended to answer the following questions: 1) are there elements which indicate social disparities structurally produced that are related to the academic and professional trajectories of individuals socially entitled as black, mulatto and white? 2) Are there elements indicating racial disparities when comparing the life trajectories of those socially entitled as blacks and mulattos to those of the ones socially called whites? Three female professors participated in this research: one socially defined as white and two socially designated as blacks (a black-skinned and a mulatto). They concluded post graduation and work in different departments in a Brazilian public university. A social demographic questionnaire and a list for completing phrases were used as information was collected. The information gathered was converted into data. Data organization included a categorization process. The results showed that poverty, indicative of social disparities, was a reality for the participants during some periods of their existential trajectories, though, when considering skin color, it was verified the existence of a connection between the participants level of poverty and her skin color, and between the participants level of poverty and career choices. The results also showed that the schooling process became their path through their professional course in life and ascending social mobility; adversities that emerged along the white, the black-skinned and the mulatto womens life were overcome through support offered by relatives and friends and through the use of personal strategies; that despite the black-skinned professor finished her academic cycle, is a qualified professional who graduated in two different courses and has a post graduation degree, she is still a target for racism, displayed either explicitly, either in disguised ways; that racism toward black individuals, expressed directly or indirectly, was addressed both to the blackskinned and the mulatto women in different episodes of their lives, while the white woman was only an observer of racial social interactions in daily basis situations; that school and family are consolidated institutions that reproduce racism against blacks; that school presented itself as a contradictory social place since, although it pursues the development of citizens, it promoted social ostracism toward the participants when they were poor children attending elementary school, putting them aside during amusing activities, collaborating to the reproduction of social disparities. The results also showed a paradox, from one hand the school is an institution responsible for the upbringing of citizens, on the other hand, it presents itself as a place for the materialization of racism expressed in social interactions among classmates or between the teacher and the student, regardless the grade in which the student is; that racism against blacks is part of a subjectivity (re)construction process, though the meanings they attribute to this process differ according to their phenotypes and experiences in social relations involving a race issue; that the participants points of view toward racism and engagement in social movements against racial discrimination are related to the way racism affected their lives, as well as to the visibility of this phenomenon in the social world and/or in their personal experiences; that being a target for racism against blacks generates singularities responsible for the constitution of the individual herself and for the construction of an ethnic identity. The results of this study will help us in the understanding of racisms social and psychological aspects, in theoretical constructions about this issue, in identifying psychological and social mechanisms of social inclusion that exclude the black, in identifying ones psychological mechanisms when facing racism, in the elaboration of strategies for racism research, in providing subsidies to the creation and execution of programs that fight racism at school through curricular and extracurricular activities.